The role of laminins in cancer pathobiology: a comprehensive review - Elena Nonnast; Emilia Mira; Santos Mañes (Journal of Translational Medicine)
Abstract Laminins (LMs) are a family of heterotrimeric glycoproteins that form the structural foundation of basement membranes (BM). By acting as molecular bridges between cells and the extracellular matrix (ECM) through integrins and other surface receptors, they regulate key cellular signals that influence cell behavior and tissue architecture. Despite their physiological importance, our understanding of the role of LMs in cancer pathobiology remains fragmented. In this article, we review the diverse functions of LMs in promoting cancer cell proliferation, adhesion, and migration—critical steps in cancer metastasis. Beyond their direct effects on tumor cells, LMs influence stromal interactions and modulate tumor microenvironment dynamics, affecting processes such as angiogenesis, immune cell infiltration, cancer-associated fibroblast activation, and immune evasion. Understanding the complex roles of LMs in cancer biology, as well as their differential expression patterns in malignancies, could provide new diagnostic tools for predicting disease outcomes and pave the way for innovative therapeutic strategies, such as targeting LM-receptor interactions or modulating ECM dynamics to impede tumor growth and metastasis.